Blogger and YouTube services at a distant course "Database management system Microsoft Access" - Dmytro A. Pokryshen; Evgeniy H. Prokofiev; Albert A. Azaryan (Academy of Cognitive and Natural Sciences, 2019)
The article is devoted to the coverage of the course "Database management system Microsoft Access", an educational blog review "The development of a creative child. ІCТ", which is used as an auxiliary tool for promoting a course and teacher in the Internet, structural analysis of this blog is made. The channel location is set on YouTube video hosting and how it is used in the course on databases. Attention is drawn to the fact that theoretical and practical material is considered on real, implemented informational and analytical systems. To prepare students for the Olympiads and provide methodological help teachers of computer science are looking at tasks from databases that were offered at the All-Ukrainian Olympiads on Information Technologies, especially II, III and IV stages (offline and online Olympiads), which are located in open access to the blog and YouTube channel. The main focus of the article is devoted to the practical side of teaching teachers of computer science, experience in using the above technologies.